Crecimiento de la tasa de recuperación de los minerales de plomo, zinc y plata en la etapa de concentración de minerales de la minera volcan s.a.a. - Castillo Reyna, Katherine Palova (2012)
The present work aims to increase the recovery rate of minerals of lead, zinc and silver in the process of mining mineral concentration VOLCAN S.A.A. Based on mineralogical and metallurgical analysis, it was concluded that the ore of Lead, Zinc and Silver (common mineral), is the possibility of greater economic mineral because of its high head grades, low hardness, lower content of elements and absence of penalized Chalcantita; is concentrated obtainable with better recoveries. Using the common mineral basis of our study, 3 tests were performed at the metallurgical laboratory grinding, regrinding heavy media flotation of zinc and primary lead. Thus, the percentage optimum grinding the concentrator is 60.2%, with the regrinding of coarse mineral zinc media, resulting in better recovery thereof, with a difference of 5.94% compared to the standard test without regrinding of the media and finally to conduct a pre-flotation process the ore obtained during the primary grinding, eliminates the loss of values as lamas sobremolienda of fines. By the above we conclude that it is possible to increase the recovery rate of minerals of Pb, Zn and Ag in mining VOLCAN S.A.A., implementing processes developed during this work.